POPULASI BELALANG DI KAWASAN TAMAN SIMPANG PASAR INDUK JAKABARING KOTA PALEMBANG - Fenaldi, Ahmad; Nurjanah, Lilis; Zelika, Suciati; Wahyuni, Intan; Putri, Septa Cahyani Hasta; Rahmawati, Nadia; Wicaksono, Anggun (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2024)
Indonesia is a country that has a fairly high level of biodiversity in fauna, one of which is insects. Grasshoppers are included in the insect order Orthoptera with a total of 20,000 species. One of the problems in research on grasshoppers and their relatives in the order Orthoptera is the low level of knowledge about population, diversity, and the relationship between grasshopper presence and environmental parameters. Sampling of the locust population was carried out during the day using the capture-recapture method using insect nets. The research location is with samples taken at 4 points with a distance between one point and another about 10 meters. At each point, 1 plot is made with a size of 5 x 5 m. The number of individual locust species found in the Jakabaring Main Market Intersection Park area is worth 88 and the species diversity index of grasshoppers found in the Jakabaring Main Market Intersection Park area shows a value of 1.31 in the medium category. Based on the research that has been done, it can be concluded that there were 4 species found grasshoppers from the Orthoptera order in the Jakabaring Main Market Simpang Park area, namely Valanga nigricornis, Acrida cinerea, Omocestus viridulus and Oxya serville.